2012
DOI: 10.1016/j.bbamcr.2012.06.026
|View full text |Cite
|
Sign up to set email alerts
|

TNF-α influences the lateral dynamics of TNF receptor I in living cells

Abstract: In mammalian cells, inflammation is mainly mediated by the binding of tumor necrosis factor alpha to tumor necrosis factor receptor 1. In this study, we investigated lateral dynamics of TNF-R1 before and after ligand binding using high-density single-particle tracking in combination with photoactivated localization microscopy. Our single-molecule data indicates the presence of tumor necrosis factor receptor 1 with different mobilities in the plasma membrane, suggesting different molecular organizations. Choles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 42 publications
0
25
0
Order By: Relevance
“…QD-labelled molecules were localized by a wavelet-based method performing well for data with low SNR described recently22 and tracked over time using a simulated annealing algorithm23 to quantify single-molecule dynamics242526. We also tested the Gaussian fitting method for QD localization2728 and the Vogel algorithm for tracking individual QDs29, which yielded similar QD localization accuracy and dynamics but required much longer calculation times (the wavelet-based method worked 20 times faster with similar localization accuracy22).…”
Section: Resultsmentioning
confidence: 99%
“…QD-labelled molecules were localized by a wavelet-based method performing well for data with low SNR described recently22 and tracked over time using a simulated annealing algorithm23 to quantify single-molecule dynamics242526. We also tested the Gaussian fitting method for QD localization2728 and the Vogel algorithm for tracking individual QDs29, which yielded similar QD localization accuracy and dynamics but required much longer calculation times (the wavelet-based method worked 20 times faster with similar localization accuracy22).…”
Section: Resultsmentioning
confidence: 99%
“…SPT and super-resolution imaging methods have been used extensively to study interactions of EGFR and ErbB receptors [61,132136] and to a lesser extent TNFRs [137139]. EGFR structure, dynamics and oligomerization/interactions have been widely studied using a variety of biophysical methods which also includes localization microscopy (discussed below), number and brightness [58], FRET and/or FLIM [120,133,135,140], fluorescence recovery after photobleaching (FRAP) [141144], fluorescence correlation/cross-correlation spectroscopy (FCS, FCCS) [59,60,145], photon counting histogram (PCH) and fluorescence intensity distribution analysis (FIDA) [146], spatial intensity distribution analysis (SpIDA) [147], and single molecule photobleaching and single molecule localization and photobleaching [61,6668,135].…”
Section: New Experimental Techniques Are Changing the Game: Singlementioning
confidence: 99%
“…Heidbreder et al demonstrated that the ensemble average mobility of TNFR1 in the presence of TNFα is indistinguishable from the resting receptor, however the distribution of mobilities of individual receptor molecules showed a small but significant shift toward faster moving receptors [137]. This shift in the distribution of receptor mobilities is accompanied by an overall decrease in the percentage of nearly-immobile receptors upon the addition of ligand, and the change is exacerbated when cells are pre-treated with MβCD [137]. This raises an interesting question: If membrane cholesterol facilitates interactions between TNFR TM helices, as described above [85], does this increase in TNFR1 mobility reflect a change in the oligomeric state of the receptor?…”
Section: New Experimental Techniques Are Changing the Game: Singlementioning
confidence: 99%
“…Profiting from the pool of labelled biomolecules in a sample, a large number of single-molecule trajectories are recorded. SPT with photoactivated-localization microscopy (SPT-PALM 27 ) allows longer observation times, provides better statistics, 28,29 and allows high-density mapping of molecular movements. 30 In order to study the dynamics of retrogradely transported NF-κB in neurons at the single-molecule level, we applied SPT-PALM 27,31 and used the fluorescent protein tandem-Eos-FP (tdEos) as a reporter.…”
Section: Introductionmentioning
confidence: 99%
“…30 In order to study the dynamics of retrogradely transported NF-κB in neurons at the single-molecule level, we applied SPT-PALM 27,31 and used the fluorescent protein tandem-Eos-FP (tdEos) as a reporter. 27,28 tdEos is photoconverted from a green-fluorescent to an orange-fluorescent species by irradiation with 405 nm light. 32 Following this procedure, a small stochastic subset of the tdEos is transferred into the active (orange-fluorescent) state and tracked as single molecules.…”
Section: Introductionmentioning
confidence: 99%